The Bulgarian regional diplomacy in the context of the NATO enlargement toward the Balkans - Angelov, Ángel (Papeles del Este, 2004)
This policy paper is analysing the Bulgarian strategy to join NATO and it pays a special attention to its efforts for developing of good-neighbourly relations. The aim is to demonstrate the importance of the active regional diplomacy for the membership in NATO and the dependence of the way Bulgaria, as an applicant for membership, conducts its regional diplomacy from the general foreign policy priorities. The activities of the Bulgarian regional diplomacy will be presented in comparison with the diplomatic behaviour of its neighbour Romania in the context of the NATO’s enlargement toward the Balkans. The paper consists of two main parts, the first one is analysing the ratio behind the process of the NATO’s enlargement toward the Balkans and the challenges and trends that are connected with this process. This part is ending with an elaboration on the NATO’s admission requirements. The second part is taking a closer look on the developing of bilateral relations between Bulgaria and its immediate neighbours.